2015
DOI: 10.1093/wber/lhv037
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Road Infrastructure in Low- and Middle-Income Countries

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…The operation and management of infrastructure have been the concern of an increasing number of scholars. Wang et al identified the emerging trends of the impacts of transportation infrastructure on sustainable development based on a scientometric review; they found that cost overrun and that the cost of infrastructure investments in poor countries should be highly regarded [3]. Hulten pointed out that low-and middle-income countries are paying a growth penalty, over one-quarter of the differential growth rate between these regions and developed countries can be attributed to the difference in the effective use of infrastructural resources [4].…”
Section: Introductionmentioning
confidence: 99%
“…The operation and management of infrastructure have been the concern of an increasing number of scholars. Wang et al identified the emerging trends of the impacts of transportation infrastructure on sustainable development based on a scientometric review; they found that cost overrun and that the cost of infrastructure investments in poor countries should be highly regarded [3]. Hulten pointed out that low-and middle-income countries are paying a growth penalty, over one-quarter of the differential growth rate between these regions and developed countries can be attributed to the difference in the effective use of infrastructural resources [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the dispersion in the database could be explained by differences in the measurement of roads-for example, using costs per square metre compared to costs per metre-or estimated versus contracted or actual costs. Collier et al (2016) show that the ranking is largely unaffected when using different levels of unit costs. What drives these differences in the costs of construction and maintenance projects across countries?…”
Section: What Do We Know About Differences In Unit Costs?mentioning
confidence: 99%
“…The lack of overview of the costs of construction for a particular country also means that it is difficult to compare a set of bids for a project with similar projects. To illustrate the magnitude in differences in construction costs for similar activities, Table 3.3 (reproduced from Collier et al 2015) shows the unit cost per kilometre of an asphalt overlay of 40-59 mm across countries. The upper panel shows projects undertaken in the period 1996-8 and the lower panel shows activities undertaken between 2005-7.…”
Section: What Do We Know About Differences In Unit Costs?mentioning
confidence: 99%
“…There is, however, evidence from a large sample of countries that higher construction costs are significantly associated with poorer road infrastructure. A 10 per cent increase in unit road-construction costs, for example, is associated with a country-level reduction of 0.7 per cent in the kilometres of paved roads per person and a 0.4-point reduction in the quality of the trade-and transport-related infrastructure index component of the World Bank Logistics Performance Index (Collier, Kirchberger, and Söderbom 2016).…”
Section: The Construction Sectormentioning
confidence: 99%